2022
DOI: 10.1051/0004-6361/202142352
|View full text |Cite
|
Sign up to set email alerts
|

GOODS-ALMA 2.0: Starbursts in the main sequence reveal compact star formation regulating galaxy evolution prequenching

Abstract: Compact star formation appears to be generally common in dusty star-forming galaxies (SFGs). However, its role in the framework set by the scaling relations in galaxy evolution remains to be understood. In this work we follow up on the galaxy sample from the GOODS-ALMA 2.0 survey, an ALMA blind survey at 1.1 mm covering a continuous area of 72.42 arcmin2 using two array configurations. We derived physical properties, such as star formation rates, gas fractions, depletion timescales, and dust temperatures for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 170 publications
9
38
1
Order By: Relevance
“…While higher angular resolutions are required to precisely determine the causes of the high star formation efficiency in G09-83808, we attribute it to its internal properties, such as compactness and/or gravitational instabilities, that facilitate gas compression (see further discussion in Tsujita et al (2022), who found evidence of star-forming clumps within the rotating disk of this system). This is in line with recent results from Gómez-Guijarro et al (2022), who found that the most compact galaxies show the shortest depletion time and a starburst-like modes of star formation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…While higher angular resolutions are required to precisely determine the causes of the high star formation efficiency in G09-83808, we attribute it to its internal properties, such as compactness and/or gravitational instabilities, that facilitate gas compression (see further discussion in Tsujita et al (2022), who found evidence of star-forming clumps within the rotating disk of this system). This is in line with recent results from Gómez-Guijarro et al (2022), who found that the most compact galaxies show the shortest depletion time and a starburst-like modes of star formation.…”
Section: Discussionsupporting
confidence: 93%
“…This is well aligned with the derived masses of massive quiescent galaxies discovered at high redshifts (e.g., Tanaka et al 2019;Marsan et al 2022;Valentino et al 2020;Santini et al 2021;Stevans et al 2021), which also show compact sizes similar to the size of our target. This hints at a progenitor-descendant scenario between these populations of galaxies, and support other results from the literature suggesting that compact galaxies with low gas fractions and short depletion times are likely in the latest stages of a starburst episode and on the verge of quenching (e.g., van Dokkum et al 2015;Spilker et al 2016a;Puglisi et al 2021;Gómez-Guijarro et al 2022;Ikarashi et al 2022).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…With substantial stellar mass in the disk component of their hosts, a process is required to redistribute the stars that already exist in the disk to the bulge. Also, a nonnegligible fraction of the bulge mass is likely built up in situ, as evident by recent Atacama Large Millimeter/submillimeter Array detections of centrally concentrated star formation in high-z galaxies and AGNs (e.g., Puglisi et al 2019;Gómez-Guijarro et al 2022). A picture is emerging in which the bulge needs to be further assembled for galaxies and their SMBHs to align with the local relation.…”
Section: Discussionmentioning
confidence: 99%